Estimating The Exploration And Production (E&P) Industry's Rig Contract Business Owner - Radjagoekgoek, Robert Pangihutan; Awwal Muhammad Shafiu (Yuridika, 2024)
According to Article 33 of the 1945 Structure, oil and gas have the potential to greatly influence state and revenue generation sources, thereby realizing societal welfare and economic prosperity. For this reason, oil and gas have a crucial and strategic position among natural resources. As a result, a specialized work group for exploration and production (E&P) was established through the enactment of Oil and Gas Law Number 22, 2001. This organization is in charge of supervising all exploration and production-related operations. In accordance with Presidential Regulation No. 12, 2021, Procedural Instruction 007, 2017, exploration and production builders carry out the rig procurement procedure to rig providers builders with their proposal Owner Estimate's worth. There are conflicting interpretations and discrepancies in the Owner Estimate instruction problem for upstream exploration and production (E&P). Concerns pertaining to areas of law positivism that Owner Estimate provides may or may not be secret in the process. It allows for collusion during the purchasing procedure. Normative juridical analysis is used in the research to make Owner Estimates of Value and to cover regulation. Therefore, in order to achieve conformity with the agreement principle and legal certainty, it is required to alter the President's Regulation and the Summary of Procedural Instruction. In order for the specialized work group for exploration and production (E&P), the E&P builders, and the rig providers to execute upstream business flawlessly and optimally to support communal welfare, the regulation's evaluation will support legal clarity, ability, and persuasiveness.